Illumination impact on the electrical characteristics of Au/Sunset Yellow/n-Si/Au hybrid Schottky diode - Imer, A. G.; Kaya, E.; Dere, A.; Al-Sehemi, A. G.; Al-Ghamdi, A. A.; Karabulut, A.; Yakuphanoğlu, Fahrettin (Springer, 2020)
In this study, semiconductor device applications of organic material sunset yellow (SY) (C16H10N2Na2O7S2) has been investigated. The SY thin film was grown onn-Si via spin coating method and theAu/SY/n-Si/Auheterojunction was fabricated. The basic diode parameters of device were determined by the current-voltage (I-V) and capacitance-voltage (C-V) measurements at the room temperature. The values of the ideality factory (n) and barrier height (phi(b)) were evaluated as 1.15 and 0.70 eV, respectively; and series resistance (R-s) of device was found using Norde functions. The values of built in potential, donor concentration, Fermi energy level and barrier height were also estimated from the linearC(-2)-Vcurves with reverse bias room temperature and difference frequency. Furthermore,I-Vmeasurements were applied under different illuminations; some photoelectrical parameters of device were evaluated to understand the photo response properties of the device. Consequently, the results confirmed that the barrier height can be modified by interfacial SY layer, and the device can be used in optoelectronic applications such as optical sensor or photodiode.
Keywords: N-Type Silicon/Metal; I-V-T; Interface Control; Sunset Yellow; Junction; Semiconductor; Nanoparticles; Temperature; Photodiode; Mechanism